Задача оптимального синтеза относительно эволюции области - Алиев, Ф.А.; Нифтиев, А.А.; Зейналов, Дж.И. (Проблемы управления и информатики, 2013)
Розглянуто задачу оптимального синтезу, пов’язану зі змінами форми області. Стан системи описується системою диференціальних рівнянь відносно пари областей. Показано, що умови існування мінімуму функціонала, що розглядається, і обчислення оптимального керування за вхідними даними пов’язані з розв’язанням рівняння Ріккаті. The optimal synthesis problem related to the variation of the domain form is considered. The system state is described by the system of differential equations with respect to a pair of domains. It is shown that the conditions for the existence of the minimum of the considered functional and the calculation of the optimal control based on input data are connected with the solution of the Riccati matrix differential equation.